Early Carotid Occlusion After Endarterectomy in a Patient With a Mutation for MTHFR A1298C Polymorphism. Issue 3 (May 2017) - Vidale, Simone; Bellocchi, Silvio; Casiraghi, Paolo; Caronno, Roberto; Arnaboldi, Marco
Abstract : Introduction: Significant carotid stenosis is a well-documented risk factor for ischemic stroke. Carotid endarterectomy (CEA) and carotid artery stenting are effective procedures for the prevention of stroke in patients with this disease. However, the occurrence of restenosis could contribute to an increase in the risk of ischemic stroke. Case Report: A 79-year-old woman was admitted to the Neurosurgical Department to undergo a CEA because of a progressive stenosis. At the 3-month radiologic follow-up, the examinations showed a carotid restenosis. She was immediately started on a double-antiplatelet therapy. Blood samples revealed high levels of homocysteine and genetic tests showed a homozygous mutation for methylene tetrahydrofolate reductase A1298C polymorphism. Folic acid associated with pyridoxine was added to the treatment. Radiologic follow-ups showed no changes in the stenosis degree. Conclusions: Even if the association between homocysteine and carotid restenosis after CEA is unclear, an initial screening before the surgical procedure could be useful to promptly treat this condition and probably reduce the risk of this complication. In the case of homozygous mutation, the selection of patients and the appropriate therapy could reduce the risk of carotid restenosis.